What Do Deviations from Covered Interest Parity and Higher FX Hedging Costs Mean for Asia - Hong, Gee Hee (IMF Working Papers; Working Paper ;, 2019)
Asian countries have high demand for U.S. dollars and are sensitive to U.S. dollar funding costs. An important, but often overlooked, component of these costs is the basis spread in the cross-currency swap market that emerges when there are deviations from covered interest parity (CIP). CIP deviations mean that investors need to pay a premium to borrow U.S. dollars or other currencies on a hedged basis via cross-currency swap markets. These deviations can be explained by regulatory changes since the global financial crisis, which have limited arbitrage opportunities and country-specific factors that contribute to a mismatch in the demand and supply of U.S. dollars. We find that an increase in the basis spread tightens financial conditions in net debtor countries, while easing financial conditions in net creditor countries. The main reason is that net debtor countries are, in general, unable to substitute smoothly to other domestic funding channels. Policies that promote reliable alternative funding sources, such as long-term corporate bond market or stable long-term investors, including a 'hedging counterpart of last resort,' can help stabilize financial intermediation when U.S. dollar funding markets come under stress.